2020
DOI: 10.1021/acs.inorgchem.0c01022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Scylla and Charybdis: Maneuvering between pH Sensitivity and Excited-State Localization in Ruthenium Bi(benz)imidazole Complexes

Abstract: Bi­(benz)­imidazoles (b­(b)­im) acting as N,N-chelates in ruthenium complexes represent a unique class of ligands. They do not harbor metal-to-ligand charge-transfer (MLCT) excited states in ruthenium polypyridyl complexes upon visible-light excitation provided that no substitution is introduced at the N atoms. Hence, they can be used to steer light-driven electron-transfer pathways in a desired direction. Nonetheless, the free N atoms are susceptible to protonation and, hence, introduce highly pH-dependent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 86 publications
1
27
0
Order By: Relevance
“…At more negative potentials, i.e., between −1.6 and −2.2 V vs. Fc + /Fc, 1 – 4 feature three reduction waves. At −1.9 V and −2.2 V vs. Fc + /Fc the terminal bipyridine ligands become reduced 34 , 35 , while the first reduction in the mononuclear complexes is localized on the BL. For the alkynyl complexes 1 and 2 , this reduction (−1.6 V vs. Fc + /Fc) is shifted anodically by ~100 mV compared to the triazole complexes 3 and 4 at −1.7 V vs. Fc + /Fc.…”
Section: Resultsmentioning
confidence: 99%
“…At more negative potentials, i.e., between −1.6 and −2.2 V vs. Fc + /Fc, 1 – 4 feature three reduction waves. At −1.9 V and −2.2 V vs. Fc + /Fc the terminal bipyridine ligands become reduced 34 , 35 , while the first reduction in the mononuclear complexes is localized on the BL. For the alkynyl complexes 1 and 2 , this reduction (−1.6 V vs. Fc + /Fc) is shifted anodically by ~100 mV compared to the triazole complexes 3 and 4 at −1.7 V vs. Fc + /Fc.…”
Section: Resultsmentioning
confidence: 99%
“…However, structural modification of the bpy‐ligands, such as with electron donating groups, might tunes the relative electron acceptor potentials in Ru sufficiently to allow a stepwise double reduction on the target ligand. Alternatively, the electron deficient bipyridyl ligand can be replaced by electron rich ligands, such as, for example, carbene or biimidazole ligands, in order to localize the excited‐state relaxation and redox processes on the desired ligand sphere as shown very recently in the literature [67–71] …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the electron deficient bipyridyl ligand can be replaced by electron rich ligands, such as, for example, carbene or biimidazole ligands, in order to localize the excited-state relaxation and redox processes on the desired ligand sphere as shown very recently in the literature. [67][68][69][70][71]…”
Section: Excited-state Relaxation and Site-specific Multi-electron St...mentioning
confidence: 99%
“…For bim and bbim systems, deprotonation of the ligands caused a complete loss of the emission and a bathochromic shift of the MLCT absorption maximum (by 0.45 eV). , Contrarily, the excited-state lifetimes of 4 H -im-derived complexes shorten upon protonation of the 4 H -imidazole ligand. , This limits their applicability in systems for solar fuel generation, where drastic pH changes might occur during the catalytic turnover. In case of Ru­(II) complexes bearing ip-derived ligands, it was found that changes in the protonation state of the imidazole induce changes in the electronic configuration of the lowest excited-state, ultimately affecting the excited-state lifetime and emission properties. However, it was found that protection of the acidic protons of the imidazole unit, e.g ., the substitution of the N,N ′-acidic protons of bim and bbim ligands by a propylene group or substitution of the N -acidic proton of ip derivatives, yielded complexes with pH-invariant properties and prolonged excited-state liefetimes. Hence, this strategy allowed us to keep the favorable properties of the complexes ( i.e. , high molar absorptivity in the visible region and sufficiently long-lived excited states) at various pH values.…”
Section: Introductionmentioning
confidence: 99%